Calculation For Multipole Mixing Ratios OF Gamma Transitions From Deformation Levels IN 152Sm Nucleus - Hady, F.1\'1. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In the  present  work  , the a2 - ratio  method  has  been used  to calculate the multipole mixing  ratios , 5 - values â€¢ of y - transitions from excited levels of deformation  nucleiL-. ( 152Sm ) .The results obtained confirm the validity of this method in calculating the o - values .The  present  results are in good  agreement  with  those  of the experimental  results,   ref.( I ,2)  , and   of  theoretical   results   using interaction  boson model (IBM-I) ,ref. (5).